Prevalence of selective non-communicable diseases and their risk factors among post-menopausal women residing in slum areas of Bhubaneswar city, Odisha - Sai C Das; B C Das; Irfana; Shalini Ray; Surendra; Prabhu (Wolters Kluwer Medknow Publications, 2015)
Background: Non-communicable diseases (NCDs) represent the biggest threat to women's health worldwide. Deaths of women from NCDs during their most productive years (40-60 years) can result in tragedy for families and catastrophic expenditure. Therefore, this present study was undertaken to estimate the prevalence of selected NCDs & risk factors in post-menopausal women residing in different slums of Bhubaneswar city and to assess their current health status after attaining menopause. Methods: This cross- sectional study was conducted among 240 postmenopausal women residing in slums of Bhubaneswar city, Odisha. For assessment of risk factors for NCDs, B.M.I estimation was done; blood pressure was measured according to standard guidelines and depression and anxiety was measured by clinical psychologist using Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HAM-A). A predesigned and pretested questionnaire was administered to assess various post-menopausal related symptoms. Results: Overall, 70.5% of women were overweight, 17.8% of subjects were hypertensive and pre-hypertensive (57.2%). Prevalence of depression and anxiety was found to be 22% and 27.9%. Addiction to beetle chewing was found among 40% of subjects. The most common complaints of postmenopausal women were irritability (84.1%), muscle or joint pain (74.1%), palpitation (65.4%) hot flushes (60%) and night sweats (54.1%). Conclusion: This study reveals that NCDs and their risk factors are common among post-menopausal women and there is a need for timely screening and treatment for those conditions.